Primary neurolymphomatosis presenting as foot drop: A rare case report - Neha Bakshi; Vineeta Chand; Rajiv Anand; Rajan Duggal (Indian Journal of Pathology and Microbiology)
Neurolymphomatosis (NL) is the direct infiltration of the peripheral nervous system (PNS) by lymphoma cells and represents the least common form of PNS involvement by lymphoma. Clinical presentation is varied, and early diagnosis remains challenging. Nerve biopsy remains the diagnostic gold standard, use of magnetic resonance imaging (MRI) and fluorodeoxyglucose–positron emission tomography (FDG-PET) may help in diagnosis and selecting targets for biopsy. We report an account of an older male patient who presented with subacute onset multifocal neuropathy involving bilateral lower limbs and left foot drop. The patient was initially misdiagnosed as chronic inflammatory demyelinating polyneuropathy; however radiological assessment revealed fusiform thickening of the L5 nerve root and biopsy from the site revealed extensive infiltration by diffuse large B cell type non-Hodgkin lymphoma (NHL). High index of suspicion is vital to ensure correct diagnosis, timely treatment, and to improve patient survival.